Antimicrobial‐resistant bacterial infections from foods of animal origin: understanding and effectively communicating to consumers. Issue 1 (29th March 2019) - Ritter, G. Donald; Acuff, Gary R.; Bergeron, Gilles; Bourassa, Megan W.; Chapman, Benjamin J.; Dickson, James S.; Opengart, Kenneth; Salois, Matthew Jude; Singer, Randall S.; Storrs, Carina
Abstract: Consumers are increasingly interested in the attributes of the food they consume. This includes what is in the food and how it was raised; and at least some consumers are willing to pay a premium for products with specific attributes. However, the current plethora of labels on the market does not adequately address this issue; rather than providing actionable information, most labels add to the consumer confusion. In addition, there is a tendency toward "absence labels" that can contribute to a negative consumer perception of conventional products that may or may not include the attribute in question. Communication with consumers about the complex and highly technical issue of antimicrobial resistance (AMR) is challenging, and experiences from communication efforts about food safety–related issues demonstrate exactly how challenging this is to communicate clearly. General lessons learned from the science of risk communication can help guide efforts to communicate about the challenging issue of AMR. There are efforts underway to chart out a new approach. A new labeled animal production certification program is under development to provide choice for consumers, while reducing consumer confusion, which mandates antibiotic stewardship practices. Abstract : This article will describe the risk of AMR infection from farm use of antibiotics, how to effectively communicate this to consumers, and new steps that are being taken to clarify voluntary labeling of foods of animal origin.